PENGENDALIAN KEBAKARAN HUTAN DI KPH MADIUN PERUM PERHUTANI UNIT II JAWA TIMUR Forest Fire Management in KPH Madiun Perum Perhutani Unit II East Java - Bambang Hero Saharjo; Elga Tiara Putra (Jurnal Silvikultur Tropika, 2017)
Forest fires bring substantial losses in many aspects, especially for forest resources. Therefore, forest fire management should take into account at each of Indonesian forest area. KPH Madiun has suffered from a large forest fire in the recent 5 years, thus research to analyze the trigger factors and an effort to manage forest fire should be gone. This research used data triangular methods for data collecting and qualitative description analyse to analyze the data. Results of this research clearly shows that forest fire in KPH Madiun was mainly came from local people activities such as, burning the forest to clear the land (43%) and due to social conflict (15%). The forest fire prepetion emphasized on social approach in community based forest management (CBFM) by planting medicinal plant and establishing the forest Danger Index (FDI) board. The local people participated in fire extinction (49%), while the other not participate yet. There was no fire truck and fire monitoring tower found in the study area. Finding and arresting the suspect behind forest fire is the most difficult thing to do in post-fire management.Key words: forest fire, local people, fire management